Method for processing and manufacturing high-temperature self-adhesive enameled aluminum flat wire for high-strength CTC
Patent Information
- Application Number
- CN202511064354.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-07-31
AI Technical Summary
Existing technologies cannot meet the requirements for high-strength CTC high-temperature self-adhesive enameled aluminum flat wire for oil-immersed power transformers. The conductivity and mechanical strength of aluminum are insufficient, and it cannot replace copper as a winding material.
The aluminum flat wire is hardened using an integral cross-section compression process, with the compression rate controlled at 40%-50%. The baking temperature and time of the acetal varnish and high-temperature epoxy self-adhesive varnish are differentiated to form a composite insulating varnish film.
The yield strength of the aluminum conductor was increased to ≥90 MPa, meeting the high strength requirements of the winding wire, ensuring that the bonding strength reaches the standard of ≥8 MPa at room temperature and ≥5 MPa at 120℃, and reducing the manufacturing cost of the transformer.
Smart Images

Figure CN120809376B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of enameled aluminum flat wire, specifically relating to a processing and manufacturing method of high-strength CTC high-temperature self-adhesive enameled aluminum flat wire. Background Technology
[0002] Currently, copper is the primary material used in the winding design of oil-immersed power transformers in China. This is mainly due to copper's excellent electrical conductivity and high mechanical strength. The mechanical strength of the winding directly affects the transformer's short-circuit withstand capability and is one of the key factors in ensuring the stable operation of the transformer.
[0003] However, copper has significant limitations in its application: my country has relatively scarce copper resources, and the price of copper is more than three times that of aluminum, which leads to high design and manufacturing costs for transformers, hindering the industry's low-cost development.
[0004] If aluminum is considered as a substitute for copper, it can alleviate cost pressure, but aluminum itself has obvious shortcomings in performance: its electrical conductivity is only about 61.5% of that of copper, and the difference in mechanical strength is significant - the yield strength of normal copper wire is 80-100 MPa, while the yield strength of normal aluminum is only 30-50 MPa, about half that of copper, which is difficult to meet the design requirements of existing transformers.
[0005] Against this backdrop, a specific market demand emerged: a customer requested that the windings for oil-immersed transformers utilize 1.70×4.25mm×25 strands of high-strength CTC high-temperature self-adhesive enameled aluminum flat wire, requiring a conductor yield strength of over 90 MPa and an adhesion strength of ≥8 MPa at room temperature and ≥5 MPa at 120℃. However, with current technology, the conventional yield strength of aluminum conductors is only 30-50 MPa, and there are no mature standards or process experience for achieving high-temperature self-adhesion and meeting the aforementioned adhesion strength standards for enameled aluminum wire. Existing technology cannot meet this design requirement.
[0006] Therefore, developing a high-strength CTC fabrication method using high-temperature self-adhesive enameled aluminum flat wire for oil-immersed power transformers that can meet the above performance requirements has become an urgent problem to be solved in the industry. Summary of the Invention
[0007] The purpose of this invention is to provide a method for processing and manufacturing high-strength CTC high-temperature self-adhesive enameled aluminum flat wire, so as to solve the problems existing in the prior art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for processing and manufacturing high-strength CTC high-temperature self-adhesive enameled aluminum flat wire, comprising the following steps: Material preparation: Semi-finished products are produced using an extrusion process; Bare aluminum flat wire laying and straightening; Hardening treatment: First, the conductor is hardened using an integral cross-section compression process, with the cross-section compression rate controlled at 40% to 50%; then, the conductor is hardened using an integral cross-section compression process, with the cross-section compression rate controlled at 40% to 50%; and the dimensional difference in the thickness direction is controlled at ≤0.01mm. Coating: The insulating varnish adopts the structure of acetal varnish + high-temperature epoxy self-adhesive varnish; the baking temperature of acetal varnish is controlled at 380℃-400℃, the baking temperature of high-temperature epoxy self-adhesive varnish is controlled at 360℃-380℃, and the baking time of each baking is controlled at 0.7-0.8 minutes. Pulling and winding: The painted wire is pulled and wound onto the winding reel to form the finished product; Performance Testing: Each batch of conductors undergoes tests for adhesion, flexibility, yield strength, tensile strength, elongation, adhesive strength, and resistivity. The test parameters must meet the following requirements: Adhesion: After the sample is cut and stretched by 15%, the amount of paint film lifting ≤ 0.4b; Flexibility: After the wide and narrow sides of the enameled aluminum flat wire sample are bent 180° at rod diameters of 1a and 1.5b respectively, the paint film should not crack; Yield strength ≥ 90 MPa; Tensile strength ≥ 90 MPa; Elongation ≤ 6.0%; Adhesive strength: ≥ 8 MPa at room temperature and ≥ 5 MPa at 120℃; Resistivity at 20℃ ≤ 0.02801 Ω・mm² / m, and conforms to the requirements of IEC standard 60317-0-9.
[0009] Preferably, the overall cross-section compression process compresses the overall dimensions of the conductor in both the width and thickness directions.
[0010] Preferably, in the hardening treatment, the cross-sectional compression rate of the first and second overall cross-sectional compression processes is within the range of 40% to 50%.
[0011] Preferably, in the painting step, the acetal paint and the high-temperature epoxy self-adhesive paint are baked at different temperatures: the acetal paint is baked at 380℃-400℃, and the high-temperature epoxy self-adhesive paint is baked at 360℃-380℃.
[0012] Preferably, in the painting step, the baking time for a single baking session is strictly controlled to be 0.7-0.8 minutes.
[0013] Preferably, in the performance test, the adhesive strength must simultaneously meet the requirements of ≥8 MPa at room temperature and ≥5 MPa at 120°C.
[0014] Preferably, in the performance test, the resistivity at 20°C needs to be ≤0.02801Ω・mm² / m.
[0015] The beneficial effects of this invention are as follows: By using an integral cross-section compression process (compression rate of 40%~50%) to harden extruded aluminum flat wire, this invention effectively solves the problem that the yield strength of aluminum conductors can only reach 75 MPa under traditional hardening methods and is prone to lattice fracture and surface defects. This increases the yield strength of aluminum conductors to ≥90 MPa, while ensuring that the surface quality and resistivity performance of aluminum material meet the standards, thus satisfying the high strength design requirements of oil-immersed power transformers for winding wires.
[0016] In the painting process, the baking temperatures of acetal varnish (380℃-400℃) and high-temperature epoxy self-adhesive varnish (360℃-380℃) are differentiated, and the single baking time is limited to 0.7-0.8 minutes. This avoids the decrease in yield strength caused by the painting process and ensures that the bonding strength meets the standards of ≥8 MPa at room temperature and ≥5 MPa at 120℃. This method achieves aluminum substitution for copper, reduces transformer manufacturing costs, improves the short-circuit withstand capability of the windings, and fills a gap in related processes. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the mold structure in this invention; Figure 2 This is a structural schematic diagram of the product of the present invention. Detailed Implementation
[0018] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.
[0019] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicating orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this invention. Furthermore, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, features defined with "first," "second," etc., may explicitly or implicitly include one or more of that feature. In the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0020] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," "fixed connection," and "fixed connection" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art will understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0021] The specific embodiments of the present invention will now be described in detail with reference to the accompanying drawings and preferred embodiments.
[0022] A method for manufacturing high-strength CTC high-temperature self-adhesive enameled aluminum flat wire, the specific implementation steps are as follows: Material preparation: Semi-finished bare aluminum flat wire billets are produced using an extrusion process. Aluminum materials meeting purity requirements are selected, and the aluminum billets are extruded into preliminarily shaped bare aluminum flat wires using extrusion equipment. This ensures that the cross-sectional dimensions of the billets meet the requirements of subsequent processing allowances, providing a foundation for subsequent hardening treatment.
[0023] Bare aluminum flat wire feeding and straightening: The extruded bare aluminum flat wire blank is placed on the feeding frame and the wire is released smoothly through the feeding device; at the same time, the bare aluminum flat wire is straightened by the straightening machine. Through the synergistic action of multiple sets of straightening rollers, defects such as bending and warping of the wire are eliminated, so that the straightness of the wire meets the requirements of subsequent processing and ensures the stability of subsequent hardening and painting processes.
[0024] Hardening treatment: The straightened bare aluminum flat wire is subjected to two hardening treatments using an integral cross-section compression process.
[0025] First hardening treatment: Use a special wire drawing die (the die structure is shown in Figure 1, including the appropriate wire drawing die fillet) to compress the overall cross-section of the wire. During the compression process, the overall dimensions of the wire in the width and thickness directions are compressed at the same time, and the cross-section compression rate is controlled to be 40% to 50% (for example, if the original cross-sectional area is S, the cross-sectional area after compression is 0.5S to 0.6S). Second hardening treatment: Based on the first compression, the overall cross-section compression process is used again, and the cross-section compression rate is controlled at 40% to 50%. The thickness direction dimension of the conductor is monitored by precision measuring tools (such as micrometers) to ensure that the difference in thickness direction dimension is ≤0.01mm, so as to guarantee the dimensional accuracy and uniformity of the conductor.
[0026] Painting: The hardened bare aluminum flat wire is painted, and the insulating varnish adopts a composite structure of "acetal varnish + high-temperature epoxy self-adhesive varnish".
[0027] First, evenly coat the surface of the conductor with acetal varnish. Then, introduce the conductor coated with acetal varnish into the baking oven and control the baking temperature at 380℃~400℃. The baking time for each batch is 0.7~0.8 minutes (the baking time is ensured by adjusting the conductor pulling speed, for example, the pulling speed is 1.2~1.4m / min), so that the acetal varnish can be cured to form the bottom insulating film. After the bottom insulating film is cured, a high-temperature epoxy self-adhesive varnish is evenly coated on its surface. Then, the wire is introduced into another baking oven, and the baking temperature is controlled at 360℃~380℃. The baking time for each batch is also 0.7~0.8 minutes, so that the high-temperature epoxy self-adhesive varnish is cured to form a self-adhesive layer, thus completing the coating process.
[0028] Pulling and winding: The traction machine applies a stable tension to the coated wire and pulls it to the winding device. The winding reel then winds the wire according to the set winding tension and winding method, finally forming a neatly wound finished enameled aluminum flat wire.
[0029] Performance Testing: Each batch of finished conductors must undergo comprehensive performance testing. The testing methods and indicators are as follows: Adhesion: After cutting the sample, stretch it by 15% and observe the peeling part of the paint film. The peeling part should be ≤0.4b (b is the size of the narrow face of the flat line). Flexibility: The wide side of the enameled aluminum flat wire sample is bent 180° on a rod with a diameter of 1a (a is the width of the flat wire) and the narrow side is bent 1.5b on a rod with a diameter of 1.5b. The paint film should not crack. Yield strength and tensile strength: tested using a tensile testing machine, with a required yield strength ≥ 90 MPa and tensile strength ≥ 90 MPa; Elongation: Tested using a tensile testing machine, the elongation should be ≤6.0%; Adhesion strength: tested at room temperature and 120℃ respectively, requiring ≥8Mpa at room temperature and ≥5Mpa at 120℃; Resistivity: Tested using a resistivity meter at 20℃, the requirement is ≤0.02801Ω・mm² / m.
[0030] All test results must simultaneously meet the requirements of IEC standard 60317-0-9 to be considered a qualified product.
[0031] Currently, the yield strength of aluminum wires produced by extrusion is 30-50 MPa. After traditional hardening treatment, the yield strength can reach 70 MPa; if further hardening is performed, the yield strength reaches 75 MPa, but lattice fracture will occur on the aluminum surface, leading to defects; this cannot meet customer design requirements. This invention uses a process of compressing the extruded aluminum flat wire across its entire cross-section, controlling the compression rate at 40%-50%. Bare aluminum flat wires produced through this process achieve yield strength and resistivity performance that meet customer design requirements. When coating bare aluminum flat wires, the thick layer of insulating varnish requires baking and curing at a specific temperature and time to form an insulating film. Using existing coating processes results in a decrease in yield strength of approximately 20%, and the varying baking temperatures and times for different insulating varnishes lead to insufficient adhesive strength, thus failing to meet customer requirements. This invention addresses this by controlling the baking temperature of different insulating varnish materials. Specifically, the baking temperature for acetal varnish is controlled at 380℃-400℃, and the baking temperature for high-temperature epoxy self-adhesive varnish is controlled at 360℃-380℃, with a single baking time of 0.7-0.8 minutes. This process ensures both yield strength and adhesive strength of the aluminum flat wire while meeting the required yield strength. This satisfies the customer's requirement for high-strength CTC high-temperature self-adhesive enameled aluminum flat wire for oil-immersed power transformers, achieving yield strength and adhesive strength comparable to normal copper conductors while meeting electrical performance requirements. Furthermore, it improves the short-circuit withstand capability of transformer windings and reduces the design and manufacturing costs of oil-immersed transformers. To date, there are no publicly available publications documenting the use of a process involving overall cross-sectional compression to control the compression rate at 40%-50% and the simultaneous application of different baking temperatures to different insulating varnishes.
[0032] The "overall cross-section compression process, which controls the compression rate at 40%-50% and uses different baking temperatures for different insulating varnishes" adopted in this invention was developed through repeated research and is creative.
[0033] The invention controls the compression rate to 40%-50% for the overall cross-section compression process. In the traditional aluminum conductor hardening process, after the cross-section elongation reaches 20%, the aluminum flat wire lattice will break, and the surface quality will be unstable. At the same time, the yield strength will also reach the limit of about 75 MPa. This cannot meet the customer's requirements for the winding wire of CTC for oil-immersed transformers.
[0034] In summary, the main distinguishing technical feature of this invention lies in the manufacturing method of high-strength CTC high-temperature self-adhesive enameled aluminum flat wire with an aluminum conductor yield strength ≥90 MPa, an enameled aluminum flat wire bonding strength ≥8 MPa at room temperature, and a bonding strength ≥5 MPa at 120°C. This method, including its process and parameters, is unique and has not been implemented in any existing publications. It provides a novel manufacturing method for high-strength CTC high-temperature self-adhesive enameled aluminum flat wire with a yield strength ≥90 MPa, a bonding strength ≥8 MPa at room temperature, and a bonding strength ≥5 MPa at 120°C, producing a new type of enameled aluminum flat wire product. The production of this high-strength CTC high-temperature self-adhesive enameled aluminum flat wire fills the gap in the production process for enameled aluminum flat wire with a yield strength ≥90 MPa, a bonding strength ≥8 MPa at room temperature, and a bonding strength ≥5 MPa at 120°C.
[0035] In summary, this method is reasonably designed, simple to operate, and has stable and reliable performance. It can effectively improve the quality and output of production, and its application effect is very significant.
[0036] It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications should also be considered within the scope of protection of this invention.
Claims
1. A method for processing and manufacturing high-strength CTC high-temperature self-adhesive enameled aluminum flat wire, characterized in that, Includes the following steps: Material preparation: Semi-finished products are produced using an extrusion process; Bare aluminum flat wire laying and straightening; Hardening treatment: First, the conductor is hardened using an integral cross-section compression process, with the cross-section compression rate controlled at 40%~50%; then, the conductor is hardened using an integral cross-section compression process, with the cross-section compression rate controlled at 40%~50%; and the difference in thickness direction dimensions is controlled at ≤0.01mm. Coating: The insulating varnish adopts an acetal varnish + high-temperature epoxy self-adhesive varnish structure; the baking temperature of the acetal varnish is controlled at 380℃-400℃, the baking temperature of the high-temperature epoxy self-adhesive varnish is controlled at 360℃-380℃, and the baking time of a single baking is controlled at 0.7-0.8 minutes. Pulling and winding: The painted wire is pulled and wound onto the winding reel to form the finished product; Performance Testing: Each batch of conductors undergoes tests for adhesion, flexibility, yield strength, tensile strength, elongation, adhesive strength, and resistivity. The test parameters must meet the following requirements: Adhesion: After the sample is cut and stretched by 15%, the amount of paint film lifting ≤ 0.4b; Flexibility: After the wide and narrow faces of the enameled aluminum flat wire sample are bent 180° at rod diameters of 1a and 1.5b respectively, the paint film should not crack; Yield strength ≥ 90 MPa; Tensile strength ≥ 90 MPa; Elongation ≤ 6.0%; Adhesive strength: ≥ 8 MPa at room temperature and ≥ 5 MPa at 120℃; Resistivity at 20℃ ≤ 0.02801 Ω·mm² / m; Where a is the width of the flat wire and b is the width of the flat wire.
2. The processing and manufacturing method according to claim 1, characterized in that, The overall cross-section compression process compresses the overall dimensions of the conductor in both the width and thickness directions.
3. The processing and manufacturing method according to claim 1, characterized in that, In the painting process, the acetal paint and the high-temperature epoxy self-adhesive paint are baked at different temperatures.
Citation Information
Patent Citations
Transformer high temperature index self-adhering transposition conductor and preparation method thereof
CN101299380A
Flat conductor for solar battery and its manufacture and connection wire for solar battery
CN1747183A
